Visible Spectrophotometric Determination of Nitazoxanide in Bulk and Pharmaceutical Dosage Forms - LAKSHMI NARAYANA, K.V.; MANOHARA, Y.N. (Asian Journal of Chemistry, 2010)
Two simple and sensitive visible spectrophotometric methods (A and B) have been developed for the quantitative estimation of nitazoxanide, in bulk drug and pharmaceutical dosages forms. Methods were based on the formation of light yellow and bluish green coloured chromogens of drug with p-dimethylaminocinnamaldehyde and folin-ciocalteu reagent, which were measured at 390 and 765 nm and linearity in the concentration range of 6-30 and 2-10 μg/mL of the drug, respectively. The developed methods were found to be precise and accurate from the statistical validation of the analysis.